User Annotations as a Context for Related Document Search on the Web and Digital Libraries - Ševcech, J.; Moŕo, R.; Holub, M.; Bieliková, M. (Informatica, 2014)
User Annotations as a Context for Related Document Search on the Web and Digital Libraries